'Does anybody have that fic…?': The fannish reclamation of the circulating library. (1st March 2021) - Xanthoudakis, Alex
Associated with frivolous reading and moral repugnance, eighteenth-century circulating libraries provided women and members of the working class easy access to novels. Almost three centuries later, fans who create and own private, file-based collections of fanfiction have reclaimed the circulating library structure. Now used to preserve the very kinds of content Victorian detractors were so against by the communities they feared would be corrupted, transformative fans (mostly women and queer folx) share copies of works from their personal collections to interested readers. These serve the dual function of archiving fic for pleasure on the part of the collector, as well as storing a stable format of the work ‐ one that is less likely to be made obsolete. Because fans do not expect these files to be returned, a private fic collection is therefore not a library at all, but an archive, one that is dependent on individual taste but connected to the community through a network of endless copying, gifting and regifting. Therefore, studying these fic collections not only gives us insight into fannish reading habits over time but also points to strategies of archiving and cultural preservation in the face of technological debt.